Fruit Physicochemical and Antioxidant Analysis of Mango Cultivars under Subtropical Conditions of Brazil - Souza, J. M. A. [UNESP]; Leonel, S. [UNESP]; Modesto, J. H. [UNESP]; Ferraz, R. A. [UNESP]; Goncalves, B. H. L. [UNESP] (Tarbiat Modares Univ, 2018)
The study of mango (Mangifera indica L.) cultivars in different regions is of great importance, due to the enormous diversity of cultivars and hybrids, as well as different soil and climatic conditions. The aim of this study was to evaluate the physicochemical characteristics and bioactive compounds of mango fruits under subtropical conditions. The experiment was conducted at the Sao Manuel Experimental Farm, School of Agriculture, Botucatu, Sao Paulo State University (UNESP), Brazil. Espada Vermelha, Keitt and Palmer cultivars were evaluated. For physical analysis, weight, longitudinal and transverse diameters, fruit shape, pulp yield, peel, seed, peel color and pulp color were evaluated. Regarding chemical characteristics and bioactive compounds, titratable acidity, soluble solids, SS/TA ratio (relationship between soluble solids and titratable acidity), reducing sugars, non-reducer, total ascorbic acid, carotenoids, flavonoids, polyphenols and antioxidant activity were determined. The results showed that Palmer and Keitt cultivars had higher physical quality, such as higher pulp yield, analyzed under subtropical conditions of Brazil. However, Palmer cultivar had higher chemical quality, which was observed in the values of SS/TA ratio, high antioxidant capacity, high ascorbic acid content, greater amount of total polyphenols, and suitable quantities of flavonoids and sugars.
Keywords: Bioactive compounds; Mangifera indica L.; Fruit quality; Phenolic compounds